Sheet, method for producing the same, metal-clad laminate, circuit board, and antenna
The sheet with a low change rate of relative permittivity, incorporating fillers and fluororesin, addresses the challenge of temperature-induced dielectric property changes in high-frequency printed wiring boards, ensuring stable performance for millimeter-wave radar antennas.
Patent Information
- Application Number
- JP2024151393
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2023-09-08
- Filing Date
- 2024-09-03
- Publication Date
- 2025-03-21
- Estimated Expiration
- 2044-09-03
AI Technical Summary
High-frequency printed wiring boards, particularly those used in millimeter-wave radar antennas for mobility, face challenges due to significant changes in dielectric properties with temperature changes, affecting circuit and antenna performance.
A sheet with a low change rate of relative permittivity (≤0.020) over a wide temperature range (-50 to 150°C) is developed, incorporating two or more types of fillers, such as silica and alumina, along with fluororesin, to maintain stable dielectric properties.
The sheet effectively minimizes performance changes due to temperature variations, ensuring stable antenna performance in applications with large temperature fluctuations.
Smart Images

Figure 2025039539000001
Abstract
Description
[Technical field]
[0001] The present disclosure relates to a sheet, a method for producing the same, a metal-clad laminate, a circuit board, and an antenna. [Background technology]
[0002] There is a demand for high-frequency printed wiring boards with low transmission loss. In such high-frequency printed wiring boards, particularly those used in antennas for millimeter-wave radar for mobility, there is a demand for small changes in relative dielectric constant due to temperature changes.
[0003] Patent Documents 1 to 3 disclose the use of two or more types of fillers in combination with a fluororesin as a material for an electronic substrate. [Prior art documents] [Patent documents]
[0004] [Patent Document 1] Patent Publication No. 2020-050860 [Patent Document 2] Patent Publication No. 2020-037662 [Patent Document 3] Patent Publication No. 2023-028091 Summary of the Invention [Problem to be solved by the invention]
[0005] The change in the dielectric properties of a dielectric due to the change in the temperature of the environment in which the dielectric is used has a significant effect on the performance of circuits and antennas. Therefore, it is preferable that the dielectric properties do not change significantly with temperature changes. The present disclosure aims to provide a sheet whose relative dielectric constant changes little with temperature changes in order to minimize the effect on antenna performance. [Means for solving the problem]
[0006] The present disclosure relates to a sheet having a rate of change in relative dielectric constant of 0.020 or less in a temperature range of -50 to 150°C, and containing two or more types of fillers. The sheet preferably has a coefficient of linear expansion (CTE) of 70 ppm / K or less. The sheet preferably has a dielectric loss tangent value of 0.0015 or less at 10 GHz. The sheet preferably has a thickness of 5 to 250 μm.
[0007] The sheet preferably contains a fluororesin. The fluororesin is preferably polytetrafluoroethylene. The filler preferably has a band gap of 2 eV or more. The content of the filler in the total amount of the sheet is preferably 30% by mass or more. The filler preferably contains at least two types selected from the group consisting of silica, alumina, boron nitride, and zirconium oxide. The above filler is preferably one of two types: silica and alumina. The silica is preferably in the form of spherical particles. The silica is preferably silica particles treated with a silane coupling agent. The silane coupling agent preferably has an aminopropyl group. The silica particles preferably have an average particle size of 10 μm or less. The alumina preferably has an average particle size of 10 μm or less. The amount of the alumina blended is preferably 10 to 50 mass % based on the total amount of alumina and silica.
[0008] The present disclosure also relates to a method for producing the above-mentioned sheet, which is characterized in that a film is formed by mixing a fluororesin and a filler. The present disclosure also provides a method for producing the above-mentioned sheet, which is characterized in that a film is formed using a composition substantially consisting of fluororesin particles and filler particles containing at least silica particles and alumina particles.
[0009] The present disclosure also relates to a metal-clad laminate having the above-mentioned sheet as an essential layer and having a metal foil layer on either or both sides. The metal foil is preferably copper.
[0010] The present disclosure also relates to a circuit board comprising the above-mentioned metal laminate. The present disclosure also relates to an antenna formed from the circuit board described above. The antenna is preferably a millimeter wave antenna for mobility applications. Effect of the Invention
[0011] The sheet of the present disclosure has a small change in dielectric constant due to temperature change, and therefore has the excellent effect of preventing performance changes due to temperature change in applications where there are large temperature changes, such as antennas for millimeter-wave radar for mobility. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0012] The present disclosure will be described in detail below. The present disclosure provides a sheet characterized in that the rate of change in dielectric constant in the temperature range of -50 to 150° C. is 0.020 or less. In other words, the dielectric constant does not change in the wide temperature range of -50 to 150° C. Therefore, there is little change in the electrical properties of the sheet.
[0013] In recent years, the number of finely formed circuits, such as millimeter-wave radar antennas, has been increasing. In such circuits, even a small change in the dielectric constant can change the electrical characteristics, which can result in operational abnormalities.
[0014] Communications in the field of mobility applications require high accuracy, so by using a sheet whose relative dielectric constant hardly changes over a wide temperature range as described above, it is possible to prevent abnormalities in communications.
[0015] In other fields, too, as wiring boards are becoming increasingly dense and finer, it is becoming increasingly important to reduce the rate of change in dielectric constant in order to prevent operational abnormalities. The present disclosure is intended to improve such problems that have not been solved by conventional techniques. In this disclosure, the rate of change in dielectric constant is a value measured by the method described in the examples.
[0016] The rate of change in the relative dielectric constant in the temperature range of −50 to 150° C. is preferably 0.020 or less, more preferably 0.018 or less, and even more preferably 0.016 or less. The lower limit is not particularly limited, but can be, for example, 0.001 or more.
[0017] The sheet of the present disclosure preferably has a linear expansion coefficient (CTE) of 70 ppm / °C or less. In this way, a sheet with a small linear expansion coefficient is preferable in that it has excellent dimensional stability and stable performance even when used under conditions of large temperature changes. The CTE is more preferably 50 ppm / °C or less, and even more preferably 40 ppm / °C or less. The lower limit of the CTE is not particularly limited, but is preferably 10 ppm / °C or more, and more preferably 18 ppm / °C.
[0018] The sheet of the present disclosure preferably has a dielectric loss tangent value of 0.0015 or less at 10 GHz. This is preferable in that the dielectric loss is low and the loss is low. The dielectric loss tangent is a value measured at 20°C, more specifically, a value measured by the method described in the examples.
[0019] The dielectric loss tangent at 10 GHz is more preferably 0.0012 or less, and even more preferably 0.0011 or less. The lower limit of the dielectric loss tangent at 10 GHz is not particularly limited, but may be, for example, 0.00001 or more.
[0020] The sheet preferably has a thickness of 5 to 250 μm. By setting the thickness within the above range, the sheet can be suitably used in a metal-clad laminate. Even if the sheet of the present disclosure is thin, it can fully achieve its purpose. The thickness is more preferably less than 230 μm, and even more preferably less than 200 μm. Furthermore, it is more preferably thicker than 15 μm, and even more preferably thicker than 30 μm.
[0021] The sheet of the present disclosure is not particularly limited in composition, but preferably contains a resin and a filler. By using such a composition, the above-mentioned specific physical properties can be obtained. The resin and the filler are each described in detail below.
[0022] (Fluorine resin) The composition of the present disclosure contains a fluororesin. Since fluororesin has low dielectric properties, it can be suitably used for the purpose of the present disclosure.
[0023] The fluororesin that can be used in the present disclosure is not particularly limited, but examples thereof include polytetrafluoroethylene (PTFE), tetrafluoroethylene [TFE] / hexafluoropropylene [HFP] copolymer [FEP], TFE / alkyl vinyl ether copolymer [PFA], TFE / HFP / alkyl vinyl ether copolymer [EPA], TFE / chlorotrifluoroethylene [CTFE] copolymer, TFE / ethylene copolymer [ETFE], polyvinylidene fluoride [PVdF], and tetrafluoroethylene having a molecular weight of 300,000 or less [LMW-PTFE]. One type may be used, or two or more types may be mixed. From the viewpoint of low dielectric properties, polytetrafluoroethylene resin (PTFE) is particularly preferable. PTFE having fibrillation properties is preferable. PTFE having fibrillation properties means PTFE that can be paste-extruded from unsintered polymer powder.
[0024] The PTFE may be modified polytetrafluoroethylene (hereinafter referred to as modified PTFE), homopolytetrafluoroethylene (hereinafter referred to as homoPTFE), or a mixture of modified PTFE and homoPTFE. From the viewpoint of maintaining good moldability of polytetrafluoroethylene, the content of modified PTFE in the polymeric PTFE is preferably 10% by mass or more and 98% by mass or less, and more preferably 50% by mass or more and 95% by mass or less. The homo-PTFE is not particularly limited, and homo-PTFE disclosed in JP-A-53-60979, JP-A-57-135, JP-A-61-16907, JP-A-62-104816, JP-A-62-190206, JP-A-63-137906, JP-A-2000-143727, JP-A-2002-201217, WO 2007 / 046345 pamphlet, WO 2007 / 119829 pamphlet, WO 2009 / 001894 pamphlet, WO 2010 / 113950 pamphlet, WO 2013 / 027850 pamphlet, etc. can be suitably used. Among these, homo-PTFE having high stretchability and disclosed in JP-A-57-135, JP-A-63-137906, JP-A-2000-143727, JP-A-2002-201217, WO 2007 / 046345, WO 2007 / 119829, WO 2010 / 113950 and the like is preferred.
[0025] The modified PTFE is composed of TFE and a monomer other than TFE (hereinafter referred to as a modified monomer). The modified PTFE may be, but is not limited to, one that is uniformly modified by the modified monomer, one that is modified at the beginning of the polymerization reaction, one that is modified at the end of the polymerization reaction, etc. The modified PTFE is preferably a TFE copolymer obtained by subjecting a small amount of a monomer other than TFE to polymerization together with TFE within a range that does not significantly impair the properties of the TFE homopolymer. The modified PTFE may be, for example, those disclosed in JP-A-60-42446, JP-A-61-16907, JP-A-62-104816, JP-A-62-190206, JP-A-64-1711, JP-A-2-261810, JP-A-11-240917, JP-A-11-240918, WO 2003 / 033555 pamphlet, WO 2005 / 061567 pamphlet, WO 2007 / 005361 pamphlet, WO 2011 / 055824 pamphlet, WO 2013 / 027850 pamphlet, etc., which can be suitably used. Among these, modified PTFEs having high stretchability and disclosed in JP-A-61-16907, JP-A-62-104816, JP-A-64-1711, JP-A-11-240917, WO 2003 / 033555, WO 2005 / 061567, WO 2007 / 005361, WO 2011 / 055824 and the like are preferred.
[0026] The modified PTFE contains TFE units based on TFE and modified monomer units based on modified monomers. The modified monomer units are a part of the molecular structure of the modified PTFE and are derived from the modified monomer. The modified PTFE contains the modified monomer units in an amount of preferably 0.001 to 0.500 mass% of the total monomer units, and more preferably 0.01 to 0.30 mass%. The total monomer units are the parts derived from all monomers in the molecular structure of the modified PTFE.
[0027] The modifying monomer is not particularly limited as long as it can be copolymerized with TFE, and examples thereof include perfluoroolefins such as hexafluoropropylene (HFP), chlorofluoroolefins such as chlorotrifluoroethylene (CTFE), hydrogen-containing fluoroolefins such as trifluoroethylene and vinylidene fluoride (VDF), perfluorovinyl ethers, perfluoroalkylethylenes (PFAE), ethylene, etc. The modifying monomer used may be one type or multiple types.
[0028] The perfluorovinyl ether is not particularly limited, and examples thereof include perfluorounsaturated compounds represented by the following general formula (1). CF 2 =CF-ORf (1)
[0029] In the formula, Rf represents a perfluoro organic group.
[0030] In this specification, a perfluoro organic group is an organic group in which all hydrogen atoms bonded to carbon atoms are replaced with fluorine atoms. The perfluoro organic group may have an ether oxygen.
[0031] An example of the perfluorovinyl ether is perfluoro(alkyl vinyl ether) (PAVE) in which Rf in the above general formula (1) is a perfluoroalkyl group having 1 to 10 carbon atoms. The number of carbon atoms in the perfluoroalkyl group is preferably 1 to 5. Examples of the perfluoroalkyl group in PAVE include a perfluoromethyl group, a perfluoroethyl group, a perfluoropropyl group, a perfluorobutyl group, a perfluoropentyl group, and a perfluorohexyl group. Preferred examples of PAVE include perfluoropropyl vinyl ether (PPVE) and perfluoromethyl vinyl ether (PMVE).
[0032] The perfluoroalkylethylene (PFAE) is not particularly limited, and examples thereof include perfluorobutylethylene (PFBE), perfluorohexylethylene (PFHE), and the like.
[0033] The modifying monomer in the modified PTFE is preferably at least one selected from the group consisting of HFP, CTFE, VDF, PAVE, PFAE and ethylene.
[0034] The fluororesin is preferably non-melt processable. Non-melt processable means that the resin does not have sufficient fluidity even when heated to the melting point or higher, and cannot be molded by a melt molding method generally used for resins. PTFE corresponds to this.
[0035] In the present disclosure, it is preferable to use such a non-melt-processable fluororesin and form it into a sheet by a molding method that fibrillates it. The molding method will be described later.
[0036] The PTFE preferably has an SSG of 2.0 to 2.3. When such a PTFE is used, a PTFE membrane having high strength (cohesion and puncture strength per unit thickness) is easily obtained. Since a PTFE having a large molecular weight has a long molecular chain, it is difficult to form a structure in which the molecular chains are regularly arranged. In this case, the length of the amorphous part increases, and the degree of entanglement between the molecules increases. When the degree of entanglement between the molecules is high, the PTFE membrane is unlikely to deform under an applied load and is considered to exhibit excellent mechanical strength. In addition, when a PTFE having a large molecular weight is used, a PTFE membrane having a small average pore size is easily obtained.
[0037] The lower limit of the SSG is more preferably 2.05, and even more preferably 2.1.The upper limit of the SSG is more preferably 2.25, and even more preferably 2.2.
[0038] Standard specific gravity (SSG) was measured by preparing a sample in accordance with ASTM D-4895-89 and measuring the specific gravity of the resulting sample by the water displacement method.
[0039] In this embodiment, the molecular weight (number average molecular weight) of the PTFE constituting the PTFE powder is, for example, in the range of 2 million to 12 million. The lower limit of the molecular weight of the PTFE may be 3 million or 4 million. The upper limit of the molecular weight of the PTFE may be 10 million.
[0040] The number average molecular weight of PTFE can be measured by a method based on standard specific gravity and a method based on dynamic viscoelasticity when melted. The method based on standard specific gravity can be performed by a water displacement method based on ASTM D-792 using a sample molded based on ASTM D-4895 98. The method based on dynamic viscoelasticity is described, for example, by S. Wu in Polymer Engineering & Science, 1988, Vol. 28, 538 and the same document, 1989, Vol. 29, 273.
[0041] The PTFE preferably has a refractive index in the range of 1.2 to 1.6. By having such a refractive index, it is preferable in terms of low dielectric constant. The refractive index can be adjusted to be within the above range by a method of adjusting the polarizability or flexibility of the main chain. The lower limit of the refractive index is more preferably 1.25, more preferably 1.30, and most preferably 1.32. The upper limit of the refractive index is more preferably 1.55, more preferably 1.50, and most preferably 1.45.
[0042] The refractive indexes are values measured using a refractometer (Abbemat 300).
[0043] Moreover, the PTFE preferably has a maximum endothermic peak temperature (crystalline melting point) of 340±7°C.
[0044] The PTFE may be a low-melting-point PTFE having a maximum peak temperature of 338°C or lower on the endothermic curve on a crystalline melting curve measured by a differential scanning calorimeter, or a high-melting-point PTFE having a maximum peak temperature of 342°C or higher on the endothermic curve on a crystalline melting curve measured by a differential scanning calorimeter.
[0045] The low melting point PTFE is a powder produced by polymerization using an emulsion polymerization method, has the above-mentioned maximum endothermic peak temperature (crystalline melting point), a dielectric constant (ε) of 2.08 to 2.2, and a dielectric tangent (tan δ) of 1.9×10-4 to 4.0×10-4. Commercially available products include Polyflon Fine Powder F201, F203, F205, F301, and F302 manufactured by Daikin Industries, Ltd.; CD090 and CD076 manufactured by Asahi Glass Co., Ltd.; and TF6C, TF62, and TF40 manufactured by DuPont.
[0046] The high melting point PTFE powder is also a powder produced by emulsion polymerization, and has the above-mentioned maximum endothermic peak temperature (crystalline melting point), a dielectric constant (ε) of 2.0 to 2.1, and a dielectric tangent (tan δ) of 1.6×10 -4 ~2.2×10 -4 As commercially available products, for example, Polyflon fine powder F104 and F106 manufactured by Daikin Industries, Ltd., CD1, CD141, and CD123 manufactured by Asahi Glass Co., Ltd., and TF6 and TF65 manufactured by DuPont can be mentioned.
[0047] The powder in which both PTFE polymer particles are secondary aggregated usually has an average particle size of 250 to 2000 μm. In particular, granulated powder obtained by granulation using a solvent is preferred from the viewpoint of improving the flowability when filling a mold during preforming.
[0048] Powdered PTFE that satisfies the above-mentioned parameters can be obtained by a conventional manufacturing method, for example, by following the manufacturing methods described in International Publication No. 2015-080291 and International Publication No. 2012-086710.
[0049] (Filler) The filler that can be used in the present disclosure is not particularly limited, and examples thereof include organic fillers selected from aramid fibers, polyphenyl esters, polyphenylene sulfide, polyimides, polyether ether ketones, polyphenylenes, polyamides, and wholly aromatic polyester resins, and inorganic fillers selected from ceramics, talc, mica, alumina, tin oxide, titanium oxide, silica, calcium carbonate, calcium oxide, magnesium oxide, zirconium oxide, potassium titanate, glass fibers, glass chips, glass beads, silicon carbide, calcium fluoride, boron nitride, barium sulfate, molybdenum disulfide, and potassium carbonate whiskers. The sheet of the present disclosure uses two or more of these in combination.
[0050] Among these, it is particularly preferable to use one containing at least two kinds selected from the group consisting of silica, alumina, boron nitride and zirconium oxide. The temperature change of the dielectric loss tangent and the relative dielectric constant is greatly related to the band gap of the filler. Basically, a low dielectric loss tangent can be realized by using a compound with a large band gap. Therefore, these compounds with a suitable band gap range can be particularly preferably used. The preferred range of the band gap is preferably 2 eV or more, next preferably 3 eV or more, next preferably 3.5 eV or more, and next preferably 4 eV or more. More preferably, a filler with 4.5 eV or more, even more preferably 5 eV or more, and particularly preferably 6 eV or more is preferably used. In addition, it is particularly preferable to use a combination of two or more of these, in that a sheet with a small temperature change of the relative dielectric constant can be obtained. Among these, silica and alumina are the most preferable. The band gap was calculated by measuring the diffuse reflectance spectrum using a UV-2600 ultraviolet-visible spectrophotometer (manufactured by Shimadzu Corporation). The measurement results were called up as spectrum data in the band gap calculation Excel macro, and after selecting the "photometric value (transmittance / reflectance)" and "n value (type of transition process)", the range that could be approximated as a tangent to a straight line near the inflection point was specified, and the band gap value was calculated using a Tauc plot.
[0051] When silica and alumina are used in combination, both have a large band gap of 5 eV or more, and therefore, by using these in combination, it is possible to particularly reduce the temperature change of the relative dielectric constant.
[0052] When the filler is a combination of silica and alumina, the silica is preferably spherical silica particles, which is preferable in that it is easy to process uniformly during drilling and has a small specific surface area and therefore low transmission loss.
[0053] The spherical silica particles refer to particles whose particle shape is close to a perfect sphere, and specifically, the sphericity is preferably 0.80 or more, more preferably 0.85 or more, even more preferably 0.90 or more, and most preferably 0.95 or more. The sphericity is determined by taking a photograph with an SEM, and using the area and perimeter of the observed particles, (sphericity) = {4π × (area) ÷ (perimeter)} 2 The closer to 1, the closer to a perfect sphere. Specifically, the average value measured for 100 particles using an image processing device (Spectris Corporation: FPIA-3000) is used.
[0054] The spherical silica particles used in the present disclosure preferably have a D90 / D10 of 2 or more (preferably 2.3 or more, 2.5 or more) and a D50 of 10 μm or less when the volume is calculated from the smallest particle size. Furthermore, it is preferable that the D90 / D50 is 1.5 or more (more preferably 1.6 or more). It is preferable that the D50 / D10 is 1.5 or more (more preferably 1.6 or more). It is more preferable that the D50 is 5 μm or less. Since the small particle size spherical silica particles can enter the gaps between the large particle size spherical silica particles, it is possible to achieve excellent filling properties and high fluidity. In particular, it is preferable that the particle size distribution has a high frequency on the side of small particle size compared to a Gaussian curve. The particle size can be measured by a laser diffraction scattering type particle size distribution measuring device. In addition, since coarse particles make it difficult to form a thin sheet, it is preferable that the coarse particles having a particle size of a certain size or more are removed by a filter or the like.
[0055] In the present disclosure, the surface area (m 2 / g) is a value based on the BET method, and can be measured using a specific surface area measuring device such as "Macsorb HM model-1208" (manufactured by MACSORB). When the sheet of the present disclosure contains two or more types of fillers, the surface area measured for the entire blended fillers falls within the above-mentioned range.
[0056] The silica particles preferably have an average particle size of 10 μm or less. If the average particle size of the silica particles is 10 μm or less, the surface roughness of the sheet is low, which is preferable. The upper limit of the average particle size of the silica particles is more preferably 8 μm or less, and even more preferably 5 μm or less. The average particle size here is the D50 value measured by a laser analysis type particle size distribution meter.
[0057] The silica particles may be treated with a silane coupling agent. By previously treating the surface, the aggregation of the silica particles can be suppressed, and the silica particles can be well dispersed in the sheet.
[0058] The silane coupling agent is not particularly limited, and any known one can be used.Specific examples include treatment with a silane coupling agent such as epoxysilane, aminosilane, isocyanatesilane, vinylsilane, acrylicsilane, hydrophobic alkylsilane, phenylsilane, and fluorinated alkylsilane having a reactive functional group, plasma treatment, and fluorination treatment.
[0059] Examples of the silane coupling agent include epoxy silanes such as γ-glycidoxypropyltriethoxysilane and β-(3,4-epoxycyclohexyl)ethyltrimethoxysilane, amino silanes such as aminopropyltriethoxysilane and N-phenylaminopropyltrimethoxysilane, isocyanate silanes such as 3-isocyanatepropyltrimethoxysilane, vinyl silanes such as vinyltrimethoxysilane, and acrylic silanes such as acryloxytrimethoxysilane. Among these, those having an aminopropyl group are preferred.
[0060] The spherical silica particles may be commercially available silica particles that satisfy the above-mentioned properties. Examples of commercially available silica particles include Denka fused silica FB grade (manufactured by Denka Co., Ltd.), Denka fused silica SFP grade (manufactured by Denka Co., Ltd.), Excelica (manufactured by Tokuyama Corporation), high-purity synthetic spherical silica particles Admafine (manufactured by Admatechs Co., Ltd.), Admanano (manufactured by Admatechs Co., Ltd.), Admafuse (manufactured by Admatechs Co., Ltd.), etc.
[0061] When the silica particles are treated with a silane coupling agent, the amount of the treatment is not particularly limited, but is preferably within the range of 0.1 to 1.5 mass %, and more preferably within the range of 0.15 to 1.0 mass %, based on the amount of the coated silica particles.
[0062] The above-mentioned alumina has good electrical insulation and thermal conductivity, and the shape and size of the alumina particles are not particularly limited, and any known alumina particles can be used. More specifically, the average particle size is preferably 10 μm or less. If the average particle size of the alumina particles is 10 μm or less, the surface roughness of the sheet is low, which is preferable. The upper limit of the average particle size of the alumina particles is more preferably 5 μm or less, and even more preferably 4 μm or less. In addition, the lower limit of the average particle size of the alumina particles is not particularly limited, but is preferably 0.5 μm or more. If the average particle size is less than 0.5 μm, the filler tends to aggregate, and sufficient effects cannot be obtained. The method for measuring the average particle size here is the same as the method for measuring the silica particles described above. The alumina particles may or may not be surface-treated. In addition, the BET specific surface area (m2 / g) is preferably 1.0 to 5.0, preferably 1.2 to 4.0, and particularly preferably 1.4 to 3.2. The oil absorption (ml / 100 g) is preferably from 10 to 40, more preferably from 15 to 30, and particularly preferably from 20 to 27. The pH is preferably from 7 to 10, more preferably from 8 to 10, and particularly preferably 9.
[0063] The mixing ratio of the silane particles and the alumina particles is not particularly limited, but for example, the amount of alumina is preferably 10 to 50% by mass based on the total amount of alumina and silica. More preferably, it is 12 to 40% by mass, and even more preferably, it is 13% to 35% by mass. By keeping it within the above range, it is preferable in that a sheet with a small temperature change in relative dielectric constant can be obtained.
[0064] The alumina particles may be commercially available alumina particles that satisfy the above-mentioned properties, such as LS-210B and LS-110F manufactured by Nippon Light Metal Co., Ltd.
[0065] The sheet of the present disclosure preferably contains 30% by mass or more of the filler relative to the total amount of the sheet. This amount is preferable in that it maintains a low dielectric constant and low loss while achieving low thermal expansion. The amount is more preferably 35% by mass or more, even more preferably 50% by mass or more, and even more preferably 55% by mass or more. There is no particular upper limit to the amount of the filler, but it is preferably 70% by mass or less, more preferably 68% by mass or less, and even more preferably 65% by mass or less.
[0066] (Sheet manufacturing method) The sheet of the present disclosure can be obtained by mixing the above-mentioned fluororesin particles and a filler and forming the mixture into a film. The manufacturing method is not limited, but can be paste extrusion molding, powder rolling molding, etc.
[0067] As described above, it is preferable to use a non-melt processable fluororesin as the fluororesin used in the sheet of the present disclosure. When such a fluororesin is used and is molded into a sheet, it is preferable to mold the sheet by fibrillating powdered PTFE as a raw material.
[0068] The powdered PTFE preferably has a primary particle size of 0.05 to 10 μm. The use of such a powder has the advantage of excellent moldability and dispersibility. The primary particle size here is a value measured in accordance with ASTM D 4895.
[0069] The powdered PTFE preferably contains 50% by mass or more, more preferably 80% by mass or more, of polytetrafluoroethylene resin having a secondary particle diameter of 500 μm or more. The PTFE having a secondary particle diameter of 500 μm or more within this range has the advantage of being able to produce a composite sheet with high strength. By using PTFE having a secondary particle diameter of 500 μm or more, a composite sheet with lower resistance and excellent toughness can be obtained.
[0070] The lower limit of the secondary particle diameter is more preferably 300 μm, and even more preferably 350 μm. The upper limit of the secondary particle diameter is more preferably 700 μm or less, and even more preferably 600 μm or less. The secondary particle diameter can be determined, for example, by a sieving method.
[0071] The powdered PTFE preferably has an average primary particle size of 50 nm or more, since a sheet having higher strength and excellent homogeneity can be obtained. More preferably, it is 100 nm or more, even more preferably, it is 150 nm or more, and particularly preferably, it is 200 nm or more. The larger the average primary particle size of PTFE, the more suppressed the increase in paste extrusion pressure when the powder is used for paste extrusion molding, and the more excellent the moldability. The upper limit is not particularly limited, but may be 500 nm. From the viewpoint of productivity in the polymerization step, it is preferably 350 nm.
[0072] The above average primary particle diameter can be determined by preparing a calibration curve of the transmittance of 550 nm projected light per unit length of an aqueous dispersion of PTFE obtained by polymerization, the polymer concentration of which is adjusted to 0.22% by mass, and the average primary particle diameter determined by measuring the unidirectional diameter in a transmission electron microscope photograph, measuring the above transmittance for the aqueous dispersion to be measured, and then based on the calibration curve.
[0073] The PTFE used in the present disclosure may have a core-shell structure.The PTFE having a core-shell structure may include, for example, modified polytetrafluoroethylene, which contains a core of high molecular weight polytetrafluoroethylene and a shell of lower molecular weight polytetrafluoroethylene or modified polytetrafluoroethylene in a particle.As such modified polytetrafluoroethylene, for example, the polytetrafluoroethylene described in JP-A-2005-527652 may be included.
[0074] The specific methods for paste extrusion molding and powder rolling molding are not particularly limited, but the general methods are described below.
[0075] (Paste extrusion molding) The method for producing the sheet may include the steps of: mixing the PTFE powder obtained by using a hydrocarbon surfactant with an extrusion aid (1a), paste extrusion molding the mixture (1b), rolling the extrudate obtained by extrusion molding (1c), drying the rolled sheet (1d), and firing the dried sheet to obtain a molded product (1e). The paste extrusion molding may also be performed by adding conventional additives such as pigments and fillers to the PTFE powder.
[0076] The extrusion aid is not particularly limited, and generally known ones can be used, such as hydrocarbon oils.
[0077] (Powder rolling molding) The sheet can also be formed by powder rolling molding. Powder rolling molding is a method in which a resin powder is fibrillated by applying a shear force to the resin powder, and then molded into a sheet. The method may include a step of subsequently firing the powder to obtain a molded body. More specifically, a step (1) of applying a shear force to a raw material composition containing a fluororesin and a filler while mixing the raw material composition. A step (2) of forming the mixture obtained by the step (1) into a bulk form; and A step (3) of rolling the bulk mixture obtained in the step (2) into a sheet. The composition can be obtained by a manufacturing method having the following steps. When forming a sheet by such powder rolling molding, it is preferable to mix only the fluororesin particles and the inorganic filler and mold the mixture.
[0078] When a sheet is manufactured by the powder rolling molding method, it is preferable to form a film using a composition that does not contain a liquid component and is essentially composed of fluororesin particles and filler particles. Here, "essentially composed of fluororesin particles and filler particles" means that the content of components other than the fluororesin particles and the filler particles is 3 mass% or less based on the total amount of the composition.
[0079] The sheet of the present disclosure may be surface-treated to increase the adhesive strength with the copper foil. The specific method of surface treatment of the sheet is not particularly limited, and any known method may be used. Conventional discharge treatments such as plasma discharge treatment, corona discharge treatment, glow discharge treatment, and sputtering treatment may be used for the surface treatment of the sheet. Among these, plasma treatment is preferred.
[0080] The plasma treatment is a treatment in which the sheet is brought into contact with plasma to etch the fluororesin on the outer surface of the sheet and add oxygen atoms, nitrogen atoms, etc. to the outer surface of the sheet. For example, the surface free energy can be controlled by introducing oxygen gas, nitrogen gas, hydrogen gas, helium gas, argon gas, or the like into the discharge atmosphere.
[0081] Alternatively, the surface to be modified may be exposed to an atmosphere of an organic compound-containing inert gas, which is an inert gas containing an organic compound, and a high-frequency voltage is applied between the electrodes to cause a discharge, thereby generating active species on the surface, and then the surface treatment may be performed by introducing a functional group of the organic compound or graft polymerizing a polymerizable organic compound.
[0082] The organic compound in the organic compound-containing inert gas includes polymerizable or non-polymerizable organic compounds containing oxygen atoms, such as vinyl esters such as vinyl acetate and vinyl formate; acrylic esters such as glycidyl methacrylate; ethers such as vinyl ethyl ether, vinyl methyl ether, and glycidyl methyl ether; carboxylic acids such as acetic acid and formic acid; alcohols such as methyl alcohol, ethyl alcohol, phenol, and ethylene glycol; ketones such as acetone and methyl ethyl ketone; carboxylic esters such as ethyl acetate and ethyl formate; acrylic acids such as acrylic acid and methacrylic acid. Among these, vinyl esters, acrylic esters, and ketones are preferred because the modified surface is less likely to be deactivated, that is, has a long life. In particular, vinyl acetate and glycidyl methacrylate are preferred.
[0083] The concentration of the organic compound in the organic compound-containing inert gas varies depending on the type of the organic compound, the type of fluororesin to be surface-treated, etc., but is usually 0.1 to 3.0% by volume, preferably 0.1 to 1.0% by volume, more preferably 0.15 to 1.0% by volume, and even more preferably 0.30 to 1.0% by volume. The discharge conditions may be appropriately selected depending on the desired degree of surface treatment, the type of fluororesin, the type and concentration of the organic compound, etc. Usually, the discharge amount is 50 to 1500 W·min / m 2 , preferably 70 W·min / m 2 More than 1400W min / m 2 Discharge treatment is carried out within the following range. The treatment temperature can be any temperature within the range of 0° C. to 100° C. A temperature of 80° C. or less is preferable to prevent stretching or wrinkling of the sheet.
[0084] (Laminate) The sheet of the present disclosure can be used as a sheet for printed wiring boards by laminating it with other substrates.
[0085] The sheet of the present disclosure can be used as a sheet for a circuit board by laminating it with a metal foil. A laminate may be formed by adhering a metal foil to one or both sides of the above-mentioned sheet. The present disclosure also provides a metal clad laminate having the above-mentioned sheet as an essential layer and a metal foil layer on one or both sides.
[0086] Examples of the metal foil used in the present disclosure include copper foil, gold foil, silver foil, platinum foil, ruthenium foil, etc. Among these, copper foil is preferred because it has low conductor loss.
[0087] The present disclosure also relates to a copper-clad laminate having a copper foil bonded to one or both sides of the above-mentioned sheet. As described above, the sheet of the present disclosure is particularly suitable for use in printed wiring board applications, and therefore can be suitably used as such a copper-clad laminate.
[0088] The copper foil preferably has an Rz of 2.0 μm or less. That is, the sheet of the present disclosure has excellent adhesion to a highly smooth copper foil having an Rz of 2.0 μm or less. Furthermore, the copper foil may have an Rz of 2.0 μm or less on at least the surface to be bonded to the above-mentioned sheet, and the other surface is not particularly limited in terms of Rz value. The copper foil preferably has an Rz of 2.0 μm or less, more preferably an Rz of 1.6 μm or less, and even more preferably an Rz of 1.0 μm or less. The Rz is the sum of the highest part (maximum peak height: Rp) and the deepest part (maximum valley depth: Rv). The surface roughness is the ten-point average roughness defined in JIS-B0601. In this specification, the Rz is a value measured using a surface roughness meter (product name: Surfcom 470A, manufactured by Tokyo Seiki Co., Ltd.) with a measurement length of 4 mm.
[0089] The thickness of the copper foil is not particularly limited, but is preferably in the range of 1 to 100 μm, more preferably in the range of 5 to 50 μm, and even more preferably in the range of 9 to 35 μm.
[0090] The copper foil is not particularly limited, and specific examples thereof include rolled copper foil and electrolytic copper foil.
[0091] The copper foil having Rz of 2.0 μm or less is not particularly limited, and commercially available products can be used. Examples of commercially available copper foil having Rz of 2.0 μm or less include electrolytic copper foil CF-T9DA-SV-18 (thickness 18 μm / Rz 0.85 μm) (manufactured by Fukuda Metal Foil & Powder Co., Ltd.).
[0092] The copper foil may be surface-treated to enhance the adhesive strength with the sheet of the present disclosure.
[0093] The surface treatment is not particularly limited, but includes silane coupling treatment, plasma treatment, corona treatment, UV treatment, electron beam treatment, etc., and plasma treatment is preferred. The reactive functional group of the silane coupling agent is not particularly limited, but from the viewpoint of adhesion to the resin substrate, it is preferred to have at least one selected from an amino group, a (meth)acrylic group, a mercapto group, and an epoxy group at the end. In addition, the hydrolyzable group is not particularly limited, but includes alkoxy groups such as a methoxy group and an ethoxy group. The copper foil used in the present disclosure may have an anti-rust layer (such as an oxide film such as chromate), a heat-resistant layer, etc. formed thereon.
[0094] The surface-treated copper foil having a surface treatment layer of the above-mentioned silane compound on the copper foil surface can be produced by preparing a solution containing the silane compound and then surface treating the copper foil with this solution.
[0095] The copper foil may have a roughening treatment layer on the surface from the viewpoint of increasing adhesion to a resin substrate, etc. If the roughening treatment is likely to deteriorate the performance required in the present disclosure, the amount of roughening particles electrodeposited on the copper foil surface may be reduced as necessary, or the roughening treatment may not be performed.
[0096] Between the copper foil and the surface treatment layer, one or more layers selected from the group consisting of a heat-resistant treatment layer, a rust-proofing treatment layer, and a chromate treatment layer may be provided in order to improve various properties. These layers may be a single layer or multiple layers.
[0097] The metal-clad laminate of the present disclosure may further include a layer other than the metal foil and the sheet. The layer other than the metal foil and the sheet is preferably at least one selected from the group consisting of polyimide, modified polyimide, liquid crystal polymer, polyphenylene sulfide, cycloolefin polymer, polystyrene, epoxy resin, bismaleimide, polyphenylene oxide, modified polyphenylene ether, polyphenylene ether, and polybutadiene.
[0098] The layers other than the metal foil and sheet are not particularly limited as long as they are made of the above-mentioned resins. The layers other than the metal foil and sheet preferably have a thickness in the range of 12.5 to 260 μm.
[0099] In the metal-clad laminate of the present disclosure, the metal layer may be formed on one or both sides of the roll film. Methods for forming the metal layer include a method for laminating (adhering) metal foil to the surface of the roll film, a vapor deposition method, a plating method, and the like. Methods for laminating metal foil include a method using heat pressing. The heat pressing temperature may be from the melting point of the sheet -150°C to the melting point of the sheet +40°C. The heat pressing time is, for example, 1 to 30 minutes. The plate can be manufactured by a method in which the heat pressing pressure is 0.1 to 10 MPa.
[0100] The metal-clad laminate of the present disclosure is not particularly limited in its application, and is used as a circuit board. A printed circuit board is a plate-shaped part for electrically connecting electronic components such as semiconductors and capacitor chips, while at the same time arranging and fixing them in a limited space. There is no particular limitation on the configuration of the printed circuit board formed from the present metal-clad laminate. The printed circuit board may be any of a rigid board, a flexible board, and a rigid-flexible board. The printed circuit board may be any of a single-sided board, a board, a double-sided board, and a multilayer board (such as a pulled-up board). In particular, it can be suitably used for flexible boards and rigid boards. In particular, it can be suitably used as a printed circuit board for high frequencies of 10 GHz or more.
[0101] The circuit board is not particularly limited, and can be produced by a general method using the above-mentioned metal-clad laminate.
[0102] In the metal clad laminate of the present disclosure, the metal foil layer may be formed on one or both sides of the rolled sheet. Methods for forming the metal foil layer include laminating (adhering) a metal foil to the surface of the rolled sheet, vapor deposition, plating, and the like. The method for laminating the metal foil includes a method using heat pressing, etc. The heat pressing temperature is from the melting point of the sheet -150°C to the melting point of the sheet +40°C. The heat pressing time is, for example, 1 to 30 minutes.
[0103] For example, a method for producing a copper clad laminate is characterized in that the above sheet is laminated with copper foil, heated at 180 to 390°C, and press-molded at a pressure of 0.5 to 5 MPa under vacuum or in an inert gas atmosphere, and the method comprises the steps of: laminating the above sheet with copper foil, heating the resulting mixture at 180 to 390°C, and press-molding the resulting mixture at a pressure of 0.5 to 5 MPa under vacuum or in an inert gas atmosphere.
[0104] When obtaining the above-mentioned laminate configuration, the sheet of the present disclosure is used by adhering copper foil to one or both sides. As described above, the sheet of the present disclosure has excellent adhesiveness. Therefore, it also has excellent adhesiveness to copper foil having a high smoothness of Rz 2.0 μm or less.
[0105] Conventionally, copper foils used for circuit boards have been given a certain degree of unevenness on their surfaces to ensure adhesion to insulating layers. However, in high-frequency applications, the presence of unevenness on the surface of copper foils is undesirable because it causes loss of electrical signals. The above laminate can obtain suitable adhesion even to copper foils with high smoothness, and is a laminate that can be suitably used as a circuit board.
[0106] The laminate for a circuit board is also a laminate having a metal foil layer and the above-mentioned sheet. The laminate may further have a base layer. The base layer is not particularly limited, but preferably has a fabric layer made of glass fiber and a resin film layer.
[0107] The fabric layer made of glass fibers is a layer made of glass cloth, glass nonwoven fabric, or the like. Commercially available glass cloth can be used, and glass cloth treated with a silane coupling agent is preferable to enhance affinity with fluororesin. Examples of glass cloth materials include E glass, C glass, A glass, S glass, D glass, NE glass, and low dielectric constant glass, and E glass, S glass, and NE glass are preferable because they are easily available. The weaving method of the fibers may be plain weave or twill weave. The thickness of the glass cloth is usually 5 to 90 μm, preferably 10 to 75 μm, and it is preferable to use a glass cloth thinner than the sheet to be used.
[0108] The laminate may use a glass nonwoven fabric as a fabric layer made of glass fibers. The glass nonwoven fabric is a fabric in which short glass fibers are fixed with a small amount of a binder compound (resin or inorganic substance), or a fabric in which the shape is maintained by entangling the short glass fibers without using a binder compound, and a commercially available product can be used. The diameter of the short glass fibers is preferably 0.5 to 30 μm, and the fiber length is preferably 5 to 30 mm. Specific examples of the binder compound include resins such as epoxy resins, acrylic resins, cellulose, polyvinyl alcohol, and fluororesins, and inorganic substances such as silica compounds. The amount of the binder compound used is usually 3 to 15 mass % based on the short glass fibers. Examples of the material of the short glass fibers include E glass, C glass, A glass, S glass, D glass, NE glass, and low dielectric constant glass. The thickness of the glass nonwoven fabric is usually 50 μm to 1000 μm, and preferably 100 to 900 μm. In the present application, the thickness of the glass nonwoven fabric refers to a value measured in accordance with JIS P8118:1998 using a digital gauge DG-925 (load 110 grams, face diameter 10 mm) manufactured by Ono Sokki Co., Ltd. In order to increase the affinity with the fluororesin, the glass nonwoven fabric may be treated with a silane coupling agent.
[0109] Most nonwoven glass fabrics have a very high porosity of 80% or more, so it is preferable to use a sheet that is thicker than a sheet made of fluororesin and compress it by pressure.
[0110] The fabric layer made of glass fibers may be a layer in which a glass cloth and a glass nonwoven fabric are laminated together. This allows the properties of each layer to be combined to obtain suitable properties. The fabric layer made of glass fibers may be in the form of a prepreg impregnated with a resin.
[0111] In the above laminate, the glass fiber fabric layer and the sheet may be bonded at the interface, or the glass fiber fabric layer may be partially or entirely impregnated with the sheet. Furthermore, a prepreg may be prepared by impregnating a fabric made of glass fibers with the fluororesin composition. The prepreg thus obtained may be further laminated with the sheet of the present disclosure. In this case, the fluororesin composition used in preparing the prepreg is not particularly limited, and the sheet of the present disclosure may be used.
[0112] The resin film used as the substrate layer is preferably a heat-resistant resin film or a thermosetting resin film. Examples of the heat-resistant resin film include polyimide, modified polyimide, liquid crystal polymer, polyphenylene sulfide, etc. Examples of the thermosetting resin include those containing epoxy resin, bismaleimide, polyphenylene oxide, modified polyphenylene ether, polyphenylene ether, polybutadiene, etc. The heat-resistant resin film and the thermosetting resin film may contain reinforcing fibers. The reinforcing fibers are not particularly limited, but for example, glass cloth, particularly low dielectric type, is preferable.
[0113] The heat-resistant resin film and the thermosetting resin film are not particularly limited in terms of dielectric properties, linear expansion coefficient, water absorption rate, and other properties, but for example, the dielectric constant at 20 GHz is preferably 3.8 or less, more preferably 3.4 or less, and even more preferably 3.0 or less. The dielectric loss tangent at 20 GHz is preferably 0.0030 or less, more preferably 0.0025 or less, and even more preferably 0.0020 or less. The linear expansion coefficient is preferably 100 ppm / °C or less, more preferably 70 ppm / °C or less, and even more preferably 40 ppm / °C or less. The water absorption rate is preferably 1.0% or less, more preferably 0.5% or less, and even more preferably 0.1% or less.
[0114] The metal clad laminate of the present disclosure is not particularly limited in its application, and is used as a circuit board. The present disclosure also relates to a circuit board having the metal clad laminate. A circuit board is a plate-like component for electrically connecting electronic components such as semiconductors and capacitor chips and simultaneously arranging and fixing them in a limited space. There is no particular limitation on the configuration of a circuit board formed from the sheet or metal clad laminate of the present disclosure. The circuit board may be any of a rigid board, a flexible board, and a rigid-flexible board. The circuit board may be any of a single-sided board, a board, a double-sided board, and a multilayer board (such as a pulled-up board). In particular, it can be suitably used for flexible boards and rigid boards. When the sheet of the present disclosure does not contain glass fiber or a cloth made of glass fiber, it is suitable for flexible boards. In particular, it can be suitably used as a printed circuit board for high frequencies of 10 GHz or more.
[0115] In this disclosure, the high-frequency circuit does not only refer to a circuit that transmits only high-frequency signals, but also includes a circuit that has a transmission line that converts a high-frequency signal into a low-frequency signal and outputs the generated low-frequency signal to the outside, a transmission line for supplying power to drive high-frequency compatible components, and other transmission lines that transmit signals other than high-frequency signals, which are arranged on the same plane.The circuit can also be used as a circuit board for an antenna, a filter, etc. The present disclosure also relates to an antenna formed from the circuit board, and is particularly suitable as a millimeter wave antenna for mobility such as automobiles and aircraft.
[0116] The circuit board is not particularly limited, and can be produced by a general method using the above-mentioned metal clad laminate.
[0117] The sheet and metal clad laminate of the present disclosure are used as electric and electronic components, for example, antennas used in electronic devices and communication devices such as ETC, GPS, wireless LAN, and mobile phones, high-speed transmission connectors, CPU sockets, millimeter wave and quasi-millimeter wave radars such as collision prevention radars, RFID tags, capacitors, inverter parts, cable covering materials, insulating materials for secondary batteries such as lithium ion batteries, speaker diaphragms, etc.
[0118] Examples of high-speed communication-compatible substrates include base station antenna substrates, antenna distribution substrates, substrates for RRH (Remote Radio Head) which is the radio part of a wireless base station, substrates for the control part or baseband part (BBU: Base Band Unit) of a wireless base station, transceiver substrates for high-speed communication, substrates for RNC (Radio Network Controller), substrates for high-speed transmitters, substrates for high-speed receivers, substrates for high-speed signal multiplexing circuits, substrates for WiFig using the 60 GHz band, substrates for data transfer used in servers for data centers, etc. Examples of high-speed communication-compatible substrates include antenna substrates, for example, substrates for massive multi-element antennas (Massive MIMO) for large-capacity communication required by standards after 5G. Furthermore, examples include receiving antennas for space-transmission wireless power supply using microwaves. The sheet of the present disclosure has good adhesion to unroughened copper foil, which has low transmission loss, and therefore is particularly suitable for antennas, since when a copper-clad laminate containing the sheet of the present disclosure and unroughened copper foil is processed to obtain an antenna, the gain is improved.
[0119] The sheet of the present disclosure can be used not only as an insulator for a substrate but also as an insulator for a signal line coating material, for example, as an insulating coating material (e.g., insulating tube) for a waveguide for transmitting high-speed signals, a QSFP cable for a high-speed LAN, a coaxial cable for high-speed communication (e.g., SFP+ cable, QSFP+ cable, etc.), a coaxial cable for low loss, etc.
[0120] When using such high frequencies, materials used in electrical components such as connectors and communication devices such as casings are required to have stable electrical properties such as low relative dielectric constant (εr) and low dielectric tangent (tanδ). The sheet of the present disclosure can also be used as an insulating material for such materials.
[0121] The sheet of the present disclosure can also be used as an insulating material for connector printed wiring boards that require soldering. The sheet of the present disclosure has excellent heat resistance, so problems are unlikely to occur even at high temperatures during soldering.
[0122] In dielectric waveguides, materials with low dielectric loss are required to transmit high-frequency millimeter waves or submillimeter waves with low loss. The sheet of the present disclosure can also be used as an insulating material for dielectric waveguides that transmit millimeter waves, submillimeter waves, etc. Examples of dielectric waveguides include cylindrical dielectric lines, rectangular dielectric lines, elliptical dielectric lines, tubular dielectric lines, image lines, insulator image lines, trapped image lines, rib guides, strip dielectric lines, inverted strip lines, H guides, nonradiative dielectric lines (NRD guides), etc.
[0123] In this disclosure, mobility refers to all means and methods related to movement and transportation, including automobiles in general, such as private cars, buses, taxis, and trucks, as well as two-wheeled vehicles, such as motorcycles, bicycles, and mopeds, railways, senior cars, and compact personal mobility vehicles for one person.Mobility is not necessarily limited to vehicles that move on the ground, and may also be vehicles that move in the air or underwater. EXAMPLES
[0124] The present disclosure will now be described in detail with reference to examples. In the following examples, unless otherwise specified, "parts" and "%" represent "parts by mass" and "% by mass", respectively.
[0125] (Examples 1 to 9, Comparative Examples 1 to 3) Sheet manufacturing method (paste extrusion molding) The PTFE powder (average particle size: 500μm, apparent density: 460g / L, standard specific gravity: 2.17), silica particles (Admatechs: SC6500-SQ, average particle size: 2.1μm), and alumina particles (Nippon Light Metals: LS-210B (average particle size: 3.2μm) or LS-110F (average particle size: 1.13μm)) were weighed out in the proportions shown in Table 1 and mixed in a mixer in the presence of dry ice. The temperature during mixing was below -10℃. The resulting mixed powder was mixed with 21 wt% oil (Isopar H), and then aged for about 5 hours. The aged composition was preformed under a pressure of 3 MPa, and the preformed body was extruded at 40° C. and 50 mm / min to obtain an extrusion sample. The extruded sample was rolled with two rolls (roll gap: set to 500 to 80 um) to obtain a sample with a film thickness of 125 μm. The sample was dried at 200°C for 2 hours and calcined at 360°C for 15 minutes to obtain a sheet.
[0126] Comparative Example 4 Sheets were obtained in the same manner as in Examples 1 to 9 and Comparative Examples 1 to 3, except that zinc oxide particles (manufactured by Hakusui Tech Co., Ltd.: DW-4, average particle size: 4 μm) were used instead of the alumina particles.
[0127] Example 10 Sheet manufacturing method (powder rolling molding) PTFE powder (average particle size: 500 μm, apparent density: 460 g / L, standard specific gravity: 2.17), silica particles (manufactured by Admatechs: SC6500-SQ, average particle size: 2.1 μm), and alumina particles (manufactured by Nippon Light Metals Co., Ltd.: LS-210B (average particle size: 3.2 μm) or LS-110F (average particle size: 1.13 μm)) were weighed out to obtain the mass ratio shown in Table 1, and stirred with a Wonder Crusher at room temperature with a setting of 6 for 30 seconds × 2 times. The resulting mixture was rolled with two rolls (roll gap: set to 100 μm, roll temperature: 100° C.) to obtain a sample with a film thickness of 130 μm, which was then calcined at 360° C. for 15 minutes to obtain a sheet.
[0128] Each of the obtained samples was evaluated based on the following criteria. [Dielectric constant of sheet (Dk)] Using a split cylinder type dielectric constant / dielectric loss tangent measuring device (manufactured by EM Lab), Dk at 10 GHz was measured at 10°C intervals from -50°C to 150°C. The rate of change from -50°C to 150°C was calculated from the difference between the maximum and minimum measured Dk values.
[0129] [Dissipation factor of sheet (Df)] Df was measured at 20°C and 10 GHz using a split cylinder type dielectric constant / dielectric loss tangent measuring device (manufactured by EM Lab).
[0130] Coefficient of Linear Expansion (CTE) TMA measurements were performed in tensile mode using a TMA-7100 (Hitachi High-Tech Science Corporation). A sheet cut to a length of 20 mm, width of 5 mm, and thickness of 150 μm was used as a sample piece. The distance between the chucks was set to 10 mm, and the linear expansion coefficient was calculated from the displacement of the sample from 0 to 150°C at a heating rate of 2°C / min while applying a load of 49 mN. The results are shown in Table 1.
[0131] [Table 1]
[0132] The sheet obtained in Example 1 was subjected to [sheet surface treatment], [XPS measurement of sheet surface], and [peel strength measurement] under the following conditions. As a result, the element composition (atomic%) by XPS measurement was: C1s: 43.4, N1s: 2.8, O1s; 7.1, F1s: 43.3, Si2p: 1.2. It was also confirmed that the peel strength was a high value of 11 N / cm, and that the sheet had high adhesiveness.
[0133] [Sheet surface treatment] A sheet was placed between the upper and lower electrodes in a treatment chamber (direct type plasma surface treatment device, manufactured by Air Water Corporation) equipped with upper and lower electrodes, and the inside of the treatment chamber was filled with a mixed gas atmosphere of argon, helium, nitrogen and oxygen. The sheet surface was then subjected to discharge plasma treatment for a treatment time of 36 seconds. The elemental composition of the surface-treated sheet was measured by XPS.
[0134] [XPS measurement of sheet surface] The measurements were performed using a scanning X-ray photoelectron spectroscopy (XPS / ESCA) PHI5000VersaProbeII (ULVAC-PHI, Inc.).
[0135] [Peel strength measurement] After the surface treatment, copper foil (CF-T9DA-SV-18, Rz = 0.85 μm, Rq = 0.05 μm, manufactured by Fukuda Metal Foil Powder Co., Ltd.) was placed on top and bottom of the sheet so that the treated surfaces were in close contact with the sheet, and the sheet was then pressurized and heated in a vacuum heat press (360°C, 2.5 MPa, 300 s) to prepare a sample. The obtained sample was cut into a strip of 10 mm width, and the peel strength was measured using a Tensilon universal testing machine (manufactured by Shimadzu Corporation) by gripping the unbonded portion of the strip sample with the upper and lower chucks of the Tensilon and pulling it at a speed of 50 mm per minute, and the obtained value was taken as the peel strength.
[0136] From the above results, the sheet of the present disclosure maintains a low dielectric tangent and low CTE, while having a low rate of change in relative dielectric constant of 0.020 or less in the temperature range of -50 to 150°C, and also has excellent adhesion to copper foil, making it an excellent substrate for use in high-frequency printed wiring boards, particularly as a substrate for use in antennas for millimeter-wave radar for mobility applications. [Industrial Applicability]
[0137] The sheet of the present disclosure can be particularly suitably used for high-frequency printed circuit boards.
Claims
1. A sheet characterized in that the rate of change in relative dielectric constant in the temperature range of -50 to 150°C is 0.020 or less and the sheet contains two or more types of fillers.
2. The sheet according to claim 1 , wherein the sheet has a coefficient of linear expansion (CTE) of 70 ppm / ° C. or less.
3. 3. The sheet according to claim 1 or 2, having a dielectric tangent value of 0.0015 or less at 10 GHz.
4. 3. The sheet according to claim 1 or 2, having a thickness of 5 to 250 μm.
5. 3. The sheet according to claim 1, wherein the sheet contains a fluororesin.
6. 6. The sheet according to claim 5, wherein the fluororesin is polytetrafluoroethylene.
7. 3. The sheet according to claim 1, wherein the filler has a band gap of 2 eV or more.
8. 3. The sheet according to claim 1, wherein the filler is contained in an amount of 30% by mass or more based on the total amount of the sheet.
9. 3. The sheet according to claim 1, wherein the filler comprises at least two kinds selected from the group consisting of silica, alumina, boron nitride and zirconium oxide.
10. 3. The sheet according to claim 1, wherein the filler is composed of two types of fillers: silica and alumina.
11. 10. The sheet according to claim 9, wherein the silica is in the form of spherical particles.
12. 10. The sheet according to claim 9, wherein the silica is silica particles treated with a silane coupling agent.
13. 13. The sheet according to claim 12, wherein the silane coupling agent has an aminopropyl group.
14. 10. The sheet according to claim 9, wherein the silica particles have an average particle size of 10 μm or less.
15. 10. The sheet according to claim 9, wherein the alumina has an average particle size of 10 μm or less.
16. The sheet according to claim 9, wherein the amount of the alumina is 10 to 50 mass % based on the total amount of the alumina and silica.
17. 6. The method for producing a sheet according to claim 5, wherein the film is formed by mixing a fluororesin and a filler.
18. 6. The method for producing a sheet according to claim 5, wherein the film is formed using a composition substantially consisting of fluororesin particles and filler particles containing at least silica particles and alumina particles.
19. 3. A metal-clad laminate comprising the sheet according to claim 1 or 2 as an essential layer and a metal foil layer on either or both sides.
20. 20. The metal clad laminate of claim 19, wherein the metal foil is copper.
21. A circuit board comprising the metal-clad laminate according to claim 19.
22. An antenna formed from the circuit board according to claim 21.
23. 23. The antenna of claim 22, which is a millimeter wave antenna for mobility.
24. 3. The sheet according to claim 1 or 2, which is for use in a circuit board.
Citation Information
Patent Citations
High-frequency and high-speed copper-clad plate and preparing method thereof
CN108501488A
Microwave composite dielectric substrate with high thermal stability and high dimensional stability and preparation method thereof
CN110606761A
Flexible copper-clad plate substrate, preparation method and application thereof, and circuit board
CN112679890A
High-frequency and high-speed copper-clad plate with good dielectric constant consistency and preparation and application thereof
CN113365429A
Fluoropolymer electric substrate material showing low permittivity heat coefficient
JP1995079056A